STUDENTS’ ATTITUDES TOWARDS THE USE OF AUTHENTIC MATERIALS IN EFL CLASSROOM - Harini Sugirezki Sujono (Journal of English and Education, 2017)
This present study was aimed at discovering students’ attitudes towards the use of authentic materials in EFL classroom, students’ difficulties in dealing with authentic materials, and students’ favorable authentic materials. There were 34 of the eighth-grade students in Bandung participated in this research. The data were attained through students’ questionnaires, students’ interviews, and classroom observation. The mean score of students’ questionnaire result was 51.09. It indicates that students’ attitudes towards the use of authentic materials are positive. This result was also supported by the two observers involved in this study who agreed that authentic materials could give positive impacts on all students’ element of attitudes which are cognitive, affective, and behavioral elements. Then, according to the result of students’ interview, there were five difficulties that students encountered when dealing with authentic materials: unfamiliar vocabularies appeared in authentic materials, advanced speaking fluency and intonation, low-quality of authentic materials, students’ low self-confidences, and unfamiliar authentic materials. The last, from twenty kinds of authentic materials listed in the questionnaire, songs and movies were considered as the most favorable authentic materials for EFL students.